2018
DOI: 10.1128/aac.01631-18
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Activity of Colistin in Combination with Rifampin and Azithromycin against Escherichia coli Producing MCR-1

Abstract: The lack of available antibiotics is a global public health problem due to the emergence of antimicrobial resistance. Effective therapeutic regimens are urgently needed against strains that produce the colistin resistance gene and to inhibit the emergence of resistance. In this study, we assessed the antimicrobial activity of a series of concentrations of colistin-based combinations with rifampin and/or azithromycin against three strains of , including colistin-resistant isolate MZ1501, isolate HE1704 that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…The use of antimicrobial agents in triple combinations has been explored in several recent studies [10,24,25]. As in our study, most of them included colistin, and the results were similar to ours.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The use of antimicrobial agents in triple combinations has been explored in several recent studies [10,24,25]. As in our study, most of them included colistin, and the results were similar to ours.…”
Section: Discussionsupporting
confidence: 89%
“…Li et al [10] reported the synergistic activity of rifampicin-azithromycin-colistin against E. coli producing Mcr-1. This triple antimicrobial combination was tested in vitro (time kill curves) and in an animal model (neutropenic mouse thigh model).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attributed these results to the direct effect of colistin on the bacterial outer membrane. Almost simultaneously, Fang et al28 reported similar data in tests of E. coli exposed to combinations of colistin and either azithromycin or rifampin, both in vitro and in vivo. Our data provide additional, biophysical evidence supporting those observations.…”
Section: Discussionmentioning
confidence: 78%
“…However, the emergence of plasmid-mediated colistin resistance via mobilized colistin resistance ( mcr ) genes has become a challenge to public health worldwide. MCR-positive Enterobacteriaceae have been isolated from various sources including humans, other animals, and food, most of which were Escherichia coli 25. Except for MCR, colistin resistance in Gram-negative bacteria can also be conferred by mutations in chromosomal genes associated with the biosynthesis and modification of lipopolysaccharide (LPS), and include a large array of genes and operons 68.…”
Section: Introductionmentioning
confidence: 99%